HUBUNGAN AKSES PELAYANAN KESEHATAN DENGAN KEMATIAN NEONATAL DINI - Izza Suraya; Mira Meilani; Octavia Mariance (ARKESMAS [Arsip Kesehatan Masyarakat], 2016)
Infant mortality rate is one of indicator to evaluate health care in one country. Based on Indonesian Demographic and Health Survey in 2007, a number of 93 % pregnant woman had gotAnte Natal Care during their pregnancy and 73 % of them had helped with skilled birth attedancewhen their delivery time. However, early neonatal mortality rate has been decreased in Indonesia.Therefore, this study purpose to analyze the relationship between access to health care and earlyneonatal mortality rate through Indonesia Demographic and Health Survey in year 2007. It isuse cross sectional as its design of the study. With logistic reggresion as an analytical method,this study control its confounding such as gender of babies, birth weight, mother’s age, mother’soccupation status, abortion history, parity, complication during pregancy, place of delivery, wealthindex, and place of living. The result showed thatthere was no significant relationship betweenaccess to health care and early neonatal mortality, the adjusted odds ratio was 0.42 (95 % CI;0.11 – 1.64). However, early neonatal mortality can be reduced through adequate antenatal careand increasing health facilities during delivery.